CONSUMPTION ANALYSIS OF METFORMIN, SULFONYLUREAS, AND OTHER ANTIDIABETICS DRUGS IN MOROCCO (1991-2005) - Abdessadek, Mohammed; Attari, Ahmed El; Diarra, Martin; Magoul, Rabia; Ouezzani, Seloua El; Khabbal, Youssef; Ajdi, Farida (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Type 2 Diabetes is one of the chronic diseases with a high prevalence and consequently a substantial socio-economic burden in Arab countries. In this paper, we evaluated the antidiabetic drugs consumption in Morocco during the period of 1991 to 2005, drug classes used and the effect of major studies on the consumption of the biguanides. Methods: We used sales data from the subsidiaries of the Intercontinental Marketing Service Health. The consumption volume was converted to Defined Daily Dose (DDD). Results: During 1991-2005 antidiabetic drugs consumption increased from 1.37 to 4.22 DDD/1000 inhabitants/day. In 2005 the sulfonylureas were the most consumed 2.96 DDD/1000 inhabitants/day) followed by the Biguanides (1.06 DDD/1000 inhabitants/day) and glinides 0.1 DDD/1000inhabitants/day. The largest consumption share in volume was held by sulfonylureas 72.22%, followed by the biguanides 22.22%. Conclusion: This study documents progressive changes in the consumption of antidiabetic's between 1991-2005 in Morocco. However, the significant increase in the utilization of antidiabetic's drugs is not the result of increased adherence but of increased patient number, since the use of metformin as first line therapy was still suboptimal and influenced by different studies as the Campbell and UKPDS study.Â 